2014
DOI: 10.1177/1934578x1400901232
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Murraya koenigii Fresh Leaves Using Headspace Solid Phase Microextraction – Gas Chromatography – Mass Spectrometry

Abstract: The volatile components of Murraya koenigii fresh leaves, collected from Surat Thani province, Thailand were studied by using headspace (HS) solid-phase microextraction (SPME) coupled with gas chromatography-mass spectrometry (GC-MS). The four fibers employed to extract the volatiles were polydimethylsiloxane (PDMS), polydimethylsiloxane-divinylbenzene (PDMS-DVB), carboxane-polydimethylsiloxane (CAR-PDMS) and polydimethylsiloxane-divinylbenzene-carboxane (PDMS-DVB-CAR). The volatile constituents of M. koenigii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…According to the results of the assessment of the essential oil of M. koenigii , it was found to possess Anethole (26.02%), Caryophyllene (21.15%) and α- Pinene (12.23%) as the major components. These results are in accordance with those presented in the published report of Sukkaew et al [ 27 ], wherein the essential oil obtained from the fresh leaves of M. koenigii collected from Surat Thani Province, Thailand, was found to contain β- Caryophyllene (21.4%), α- Selinene (10.2%) and α- Humulene (7.1%) and α- Pinene (4.4%) as its major components. However, in this study, the chemical composition of the essential oil of M. koenigii was distinctly different from that of previous studies.…”
Section: Resultssupporting
confidence: 92%
“…According to the results of the assessment of the essential oil of M. koenigii , it was found to possess Anethole (26.02%), Caryophyllene (21.15%) and α- Pinene (12.23%) as the major components. These results are in accordance with those presented in the published report of Sukkaew et al [ 27 ], wherein the essential oil obtained from the fresh leaves of M. koenigii collected from Surat Thani Province, Thailand, was found to contain β- Caryophyllene (21.4%), α- Selinene (10.2%) and α- Humulene (7.1%) and α- Pinene (4.4%) as its major components. However, in this study, the chemical composition of the essential oil of M. koenigii was distinctly different from that of previous studies.…”
Section: Resultssupporting
confidence: 92%
“…In this study, DVB/CAR/PDMS and PDMS/DVB fiber, which were previously shown to be most suitable for untargeted HS-SPME analysis of volatiles [ 35 ], were used for the analysis of VOCs from aerial parts of S. romana and S. montana from Croatia. In our study, the number of extracted VOCs was higher using DVB/CAR/PDMS fiber (69 compounds) than it was by using PDMS/DVB fiber (56 compounds), which is in accordance with the work of Wang et al [ 37 ], in which DVB/CAR/PDMS fiber showed better efficiency to extract volatile compounds (50 compounds) from the samples of Aquilegia japonica Nakai and H.Hara, compared to CAR/PDMS (47 compounds) and PDMS/DVB fibers (45 compounds), as well as with the work of Sukkaew et al [ 38 ], where more volatile components were extracted using DVB/CAR/PDMS fiber (51 compounds) than with PDMS/DVB (38 compounds), PDMS (38 compounds) and CAR/PDMS (37 compounds) fibers in Murraya koenigii (L.) Sprengel fresh leaves. In our study, the dominant chemical classes of volatile compounds in all samples of the two investigated Sideritis species extracted using DVB/CAR/PDMS and PDMS/DVB fibers were sesquiterpene hydrocarbons followed by monoterpene hydrocarbons, except for S. romana M in whose extract monoterpene hydrocarbons were more abundantly present.…”
Section: Discussionsupporting
confidence: 89%
“…12,14,16 A very recent study is so far the only one that aimed at identifying the volatiles not only in the hydrodistilled essential oil but also in the fresh leaves. 18 Using solid phase microextraction, 51 compounds, almost exclusively (sesqui)terpenes and (sesqui)terpenoids, were detected in the headspace above freshly picked leaf material.…”
Section: ■ Introductionmentioning
confidence: 99%